Catalogue of Syringogastridae (Diptera, Diopsoidea) - Pereira-Colavite, Alessandre; Mello, Ramon Luciano (Papéis Avulsos de Zoologia, 2018)
The catalogue of the Syringogastridae is updated, including now 21 extant species and two fossil records, all belonging to the genus Syringogaster Cresson. References to all known bibliography are given, totaling 27 records. A full list of the type-series and distribution records are also presented.